WAKAF PRODUKTIF DAN PENINGKATAN TARAF HIDUP UMAT (STUDI KASUS WAKAF PRODUKTIF DI PIMPINAN DAERAH MUHAMMADIYAH METRO) - Sabdo Sabdo; Mokhammad Samson Fajar (JURNAL KEMUHAMMADIYAHAN DAN INTEGRASI ILMU, 2023)
Productive Waqf is one of the fiqh ijtihad in the development of waqf syari'at in Islamic law. In Indonesia, the regulations governing waqf have so far been contained in the Basic Agrarian Law Number 5 of 1060, Government Regulation Number 28 of 1977 concerning Ownership of Owned Land. In addition, million is contained in the Compilation of Islamic Law (KHI), based on Presidential Instruction No.1 of 1991. Finally, the laws and regulations governing waqf legally are starting to gain a stronger position, namely the enactment of Law Number 41 of 2004 concerning Waqf. and Government Regulation of the Republic of Indonesia Number 42 of 2006 concerning Implementing Regulations of Law Number 41 of 2004 concerning Waqf. Legally, the position of waqf is very strong in religious life. However, the legal norms of productive waqf have not been immediately implemented in the lives of the people, so research is needed to examine how the relationship of productive waqf in improving the standard of living of people in the Regional Leadership of Metro City The method used is a qualitative method with a management science approach, namely planning, organizing, actuating and controlling. With the hope that it will be understood how the implementation of productive waqf in improving the standard of living of people in Metro City